Territorial benchmarking methodology: The need to identify reference regions - Mikel Navarro; Juan José Gibaja; Susana Franco; Asier Murciego (European Regional Science Association (ERSA), 2011)
Benchmarking analysis facilitates the formulation of competitiveness and innovation strategies. It also helps in the monitoring and assessment of the initiatives that have taken place. The aim of this work is to provide an instrument to facilitate the development of the three stages that benchmarking exercises should undertake, adding its application to the Basque Country as an illustrative example. The first requirement of a good benchmarking exercise is the comparability principle, that is, contrasts should take place among comparable entities. Hence, the first stage is the identification of homogeneous areas to carry out the territorial comparison. The second stage is the identification of territories or regions with best performances, which should be established through empirical comparisons. Finally, the third stage of benchmarking exercises is analysing the causes of a better or worse performance. Even if the combination of quantitative and qualitative information, together with the active participation of regional representatives, would be preferable, this paper focuses in the analysis that can be carried out with secondary data. Note: my other choice was to post this paper for the Session R -New frontiers in regional science'
Keywords: 330